Human Resource Capabilities and Local Business Models as Drivers of BUMDESMA Institutional Transformation - Katri Gentari; Sri Agustina; Susillawati (Goodwood Publishing, 2026)
Purpose: This study aims to examine the institutional transformation strategy of Joint Village-Owned Enterprises (BUMDesma) originating from the PNPM Rural Program Management Unit (UPK) and analyze the role of human resource capabilities and local business models in strengthening rural economic competitiveness. Research Methodology: This study was conducted in the Bayung Lencir Subdistrict, Indonesia, using a qualitative, single-case study approach. Data were collected through in-depth interviews with BUMDesma managers and village stakeholders, field observations, and analyses of organizational and policy documents. The data were analyzed thematically. Results: The findings show that Green Human Resource Management, Green Transformational Leadership, and Green Innovation positively and significantly impact Business Sustainability and Green Psychological Climate. Additionally, Green Psychological Climate significantly mediated the relationships between these factors and Business Sustainability. Conclusions: This study concludes that integrating human resource capabilities with adaptive local business models is essential for effective institutional transformation and the long-term sustainability of BUMDesma in Indonesia. Limitations: This study was limited to a single case, which may restrict the generalizability of the findings. Contributions: This research contributes to the community-based strategic management and rural development literature by proposing an integrative institutional transformation strategy model and offering practical insights for policymakers and BUMDesma managers to enhance the sustainable rural economic competitiveness.